Shine [videorecording (DVD)] - Hicks, Scott; Rush, Geoffrey, 1951-; Mueller-Stahl, Armin, 1930-; Redgrave, Lynn, 1943-2010 (New Line Home Video, 1997)
The story of Australian pianist David Helfgott. He experiences a nervous breakdown and is hospitalized, but later returns to the concert hall.